Structural, phonon, magnetic and optical properties of novel perovskite-like frameworks of TriBuMe[M(dca)3] (TriBuMe = tributylmethylammonium; dca = dicyanamide; M = Mn2+, Fe2+, Co2+, Ni2+). Issue 34 (12th August 2019) - Mączka, Mirosław; Gągor, Anna; Ptak, Maciej; Stefańska, Dagmara; Macalik, Lucyna; Pikul, Adam; Sieradzki, Adam
Abstract : Tributylmethylammonium metal dicyanamides exhibit huge caloric effects due to order–disorder phase transitions, and the Mn analogue shows orange emission under 420 nm excitation. Abstract : We report the synthesis, crystal structures, thermal, optical and phonon properties of four new metal dicyanamide frameworks templated using tributylmethylammonium cations (TriBuMe + ). Our results show that these compounds crystallize in a three-dimensional perovskite-like monoclinic structure, space group P 21 / n, with two inequivalent TriBuMe +, one well-ordered and the second one showing distinct disorder. DSC and X-ray diffraction show that TriBuMeMn undergoes an order–disorder structural phase transition near 380 K associated with an increase in the symmetry to the orthorhombic Pnma . Phase transitions are also observed for Ni and Fe analogues. The associated change in the phase transition entropy is very large (up to 66.7 J kg −1 K −1 for TriBuMeNi), suggesting that these compounds might be promising barocaloric materials. Raman and IR data confirm the same monoclinic structures for all compounds and show that all changes on heating to 430–450 K are reversible after cooling the samples to room temperature. Magnetic studies indicate that all studied compounds are paramagnets at least down to 2 K. Optical studies indicate that TriBuMeMn has an energy band gap of 4.95 eV and exhibits orange emission under 420 nm excitation with the activation energy for thermal quenching of 0.0673 eV.